The Impact of Inflation and Government Expenditure on Economic Growth Moderated by Gross Domestic Product - Ramadhani Kirana Putra; Afni Yeni; Rifqah Harahap; Ramadhani Hamzah; Musran Munizu (Indonesian Journal Economic Review (IJER), 2026)
This study examines the effect of inflation and government expenditure on economic growth, with gross domestic product (GDP) as a moderating variable. Economic growth reflects the overall performance of a country’s economy and is influenced by macroeconomic conditions and fiscal policy. Inflation represents price stability, while government expenditure reflects policy efforts to stimulate economic activity and support development. A quantitative approach is applied using correlation and regression techniques through path analysis, supported by EViews 12 software. Secondary data in the form of annual observations were obtained from the Central Statistics Agency (BPS) for the period 2018–2025. The analysis focuses on identifying both direct effects and the moderating role of GDP in the relationship between variables. The results show that government expenditure has a positive and significant effect on economic growth, indicating its important role in encouraging economic performance. Inflation does not show a significant effect, suggesting relatively stable price conditions during the observed period. GDP strengthens the relationship between government expenditure and economic growth, while no moderating effect is found in the relationship between inflation and economic growth.